LGBTfobia e educação: um estudo sobre os enfretamentos à violência de gênero e sexual no centro educa mais Maria Mônica Vale - SOARES, Ana Paula dos Santos (2024)
This study aims to investigate the relationship between LGBTphobia and its connection to Education in addressing gender and sexual violence. The study is conducted at "Educa Mais Maria Mônica Vale Center, a high school that is part of the Maranhão State Full-Time Education Network. It is located in the Vinhais neighborhood, in São Luís-MA. The research is focused on the following problems: how are issues related to gender identities and sexual orientation being addressed at school to stimulate a reflection on prejudice, discrimination and contribute to an atmosphere that combats gender and sexual violence? The research methodology is applied in nature with a qualitative approach, using the case study (what case study) as a method of procedure. The collection instruments used were questionnaires, conversation circles and interviews. Data interpretation was conducted through content analysis. The participants were teachers, managers and students. Theoretically, the study is based on post-structuralist authors, who defend a conception of inequalities based on existing power relations in society. The results highlight the urgency in discussing gender and sexuality issues in the school environment as a way to combat prejudice and discrimination. It is observed that the school makes its LGBTQIA+ students invisible, silencing their experiences and existences in the curriculum. It is evident that teachers do not feel prepared to address these topics, as a result of which there is a lack of acceptance for students and representation in pedagogical practices. Therefore, teacher training and the inclusion of diversity themes are essential conditions for breaking the cycle of exclusion and combating LGBT phobia in our schools.